Parenting Styles and Child's dmft Score and Behavior in Dental Clinic - Ayoub, Solafa. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Pediatric Dentistry.; Advisor: Cheen Loo.; Committee: Matthew Finkelman, Mohammad Hassan, and Gerald Swee.; Keyword: Dentistry.